Associação entre os polimorfismos do gene BCMO1 (β-caroteno 15,15'-monooxigenase 1) e as concentrações séricas de β-caroteno e retinol em diferentes etnias brasileiras - Santos, Vanessa Lorenço Peresi dos [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
Vitamin A is important in human nutrition, since deficiency is considered a serious public health and child mortality. Provitamin A carotenoids, particularly β-carotene from certain plant foods are important sources of vitamin A for many populations. During the bioconversion process carotenoids are cleaved by cytosolic enzyme β-carotene 15,15'-monooxygenase 1 (BCMO1). Two polymorphisms (Single Nucleotide Polymorphisms - SNPs) in BCMO1 gene, R267S: rs12934922 and A379V: rs7501331, were identified in ethnic populations of Caucasian, Japanese and Chinese, and it may cause reduced enzyme activity BCMO1 and justify the wide inter-individual differences in bioconversion of β-carotene into vitamin A. The aims of this study were to identify the frequency of polymorphic variants A379V and R267S/A379V of BCMO1 gene in three population groups (whites, blacks and Japanese) and evaluate the relationship between SNPs with serum β-carotene and retinol among three different ethnic groups. Each group was composed of 100 volunteers, with European, African and Japanese ancestry, and 50% were female and 50% male. Were evaluated plasmatic concentrations of β-carotene, retinol, zinc erythrocyte, lymphocytes, C-reactive protein, α-1-acid glycoprotein and dietary intake of Vitamin A. Samples of saliva and oral mucosa exfoliated cells were collected for DNA extraction with subsequent genotyping of SNPs R267S: rs12934922 and A379V: rs7501331 by RT-PCR. The frequencies of allelic variants R267S and A379V at least one T allele for individuals with European ancestry were 63.0% and 44.0%, respectively, African ancestry, 48.0% and 18.0%, respectively, and Japanese ancestry, 21.0 % and 27.0%, respectively. The results show, so unique, that the frequencies of polymorphic variants of the polymorphic variants A379V and R267S BCMO1 gene in Brazilian population groups evaluated depend on ethnicity for both SNPs. The polymorphic variants observed do not seem to ...

A vitamina A tem importância na nutrição humana, uma vez que a sua deficiência é considerada um sério problema de saúde pública e de morbimortalidade infantil. Carotenóides pró-vitamina A, particularmente o β-caroteno proveniente de determinados alimentos de origem vegetal, são importantes fontes de vitamina A para muitas populações. Durante o processo de bioconversão os carotenóides são clivados pela enzima citossólica β-caroteno 15,15'-monooxigenase 1 (BCMO1). Dois polimorfismos (Single Nucleotide Polymorphisms - SNPs) no gene BCMO1, R267S: rs12934922 e A379V: rs7501331, foram identificados em populações de etnias Caucasiana, Japonesa e Chinesa, podendo causar redução da atividade enzimática da BCMO1 e justificar a ampla diferença inter-individual na bioconversão do β-caroteno em vitamina A. Os objetivos deste estudo foram identificar a frequência das variantes polimórficas A379V e R267S/A379V do gene BCMO1 em três grupos populacionais brasileiros (brancos, negros e japoneses) e avaliar a relação entre os SNPs com as concentrações séricas de β-caroteno e retinol entre os três diferentes grupos étnicos. Cada grupo foi composto de 100 indivíduos voluntários, com ancestralidades Europeia, Africana e Japonesa, sendo 50% do gênero feminino e 50% do gênero masculino. Foram avaliadas as concentrações séricas de β-caroteno, retinol, zinco eritrocitário, linfócitos, proteína C-reativa, α-1-glicoproteína ácida e a ingestão alimentar de Vitamina A. Amostras de saliva e esfoliado de células da mucosa oral foram coletadas para a extração de DNA com posterior genotipagem dos SNPs A379V: rs7501331 e R267S: rs12934922 por RT-PCR. As frequências das variantes alélicas R267S e A379V com, pelo menos, um alelo T para os indivíduos com ancestralidade Europeia foram 63,0% e 44,0%, respectivamente, com ancestralidade Africana, 48,0% e 18,0%, respectivamente, e com ancestralidade Japonesa, 21,0% e 27,0%,...
Keywords: Polimorfismo (Genetica); Grupos etnicos; Vitamina A na nutrição humana; Caroteno; Vitamin A in human nutrition